A cost-benefit analysis on the specialization in departments of obstetrics and gynecology in Japan - Junyi Shen; On Fukui; Hiroyuki Hashimoto; Takako Nakashima; Tadashi Kimura (Health Economics Review, 2012)
In April 2008, the specialization in departments of obstetrics and gynecology was conducted in Sennan area of Osaka prefecture in Japan, which aims at solving the problems of regional provision of obstetrical service. Under this specialization, the departments of obstetrics and gynecology in two city hospitals were combined as one medical center, whilst one hospital is in charge of the department of gynecology and the other one operates the department of obstetrics. In this paper, we implement a cost-benefit analysis to evaluate the validity of this specialization. The benefit-cost ratio is estimated at 1.367 under a basic scenario, indicating that the specialization can generate a net benefit. In addition, with a consideration of different kinds of uncertainty in the future, a number of sensitivity analyses are conducted. The results of these sensitivity analyses suggest that the specialization is valid in the sense that all the estimated benefit-cost ratios are above 1.0 in any case.
Keywords: 330; cost-benefit analysis; specialization; departments of obstetrics and gynecology; sensitivity analysis; benefit- cost ratio